The Effect of an Application Online Scheduling Program on Work-life Balance of Nursing Personnel a Tertiary Hospital - tatisungnoen, kunyanut (NU Journal of Nursing and Health Sciences, 2025)
This two-group quasi-experimental research aimed to compare the mean scores of professional nurses’ perception of work-life balance in the work dimension between regular and online work scheduling. the sample consisted of 25 nursing personnel from the surgical-orthopedic ward (experimental group) and 25 nursing personnel from the medical ward (control group). The research employed a two-part instrument: Part 1: An online work scheduling program. Part 2: A questionnaire about work-life balance in the work dimension. The content validity index of the instrument was 0.96 and the reliability, Cronbach’s alpha coefficient was 0.93. Data analysis utilized descriptive statistics (frequency, percentage, mean, and standard deviation), and inferential statistics (independent t-test and dependent t-test). The results revealed that after participating in the program, the experimental group’s perception of work-life balance in the work dimension reached a high level (= 4.20, S.D. = 0.45), while the control group’s perception remained at a moderate level (= 2.97, S.D. = 0.40). A comparison of mean scores indicated that the perception of work-life balance in the work dimension among the experimental group, after participating in the online work scheduling program, was significantly higher than that of the control group (p < .05). The research results indicate that the online application work scheduling program where all nursing personnel in the unit can enter to arrange their work schedule and choose their own holidays has a positive effect on the balance of life in all aspects. Therefore, the administrators should use the online application work scheduling program as a guideline for staffing the unit and nursing personnel in the organization.